2001
DOI: 10.1054/bjoc.2001.1854
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and localization of TIMP-1 and TIMP-4 in human gliomas

Abstract: Studies have suggested that an imbalance of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) may contribute to the malignant phenotype of gliomas. In this study, we have undertaken a detailed analysis of expression of the TIMP family in normal human brain and malignant gliomas at both the mRNA and protein level. Reverse transcription-PCR (RT-PCR) analyses of total RNA from surgical tumour specimens revealed unique expression patterns for the 4 members of the TIMP family, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 47 publications
4
61
0
1
Order By: Relevance
“…Independent of its MMP inhibitory activity, TIMP-3 suppresses angiogenesis by blocking the interaction of VEGF with VEGFR-2 (Qi et al, 2003). On the other hand, TIMP-4 can either promote Tunuguntla et al, 2003) or inhibit tumour progression, depending on the nature of the tumour and mode of delivery Celiker et al, 2001;Groft et al, 2001;Zhao et al, 2004).…”
Section: Timpsmentioning
confidence: 99%
“…Independent of its MMP inhibitory activity, TIMP-3 suppresses angiogenesis by blocking the interaction of VEGF with VEGFR-2 (Qi et al, 2003). On the other hand, TIMP-4 can either promote Tunuguntla et al, 2003) or inhibit tumour progression, depending on the nature of the tumour and mode of delivery Celiker et al, 2001;Groft et al, 2001;Zhao et al, 2004).…”
Section: Timpsmentioning
confidence: 99%
“…2A, Lane 5). TIMP-4, reported to be negatively associated with astrocytoma malignancy (Rorive et al, 2006) and able to reduce glioblastoma invasion in vitro (Groft et al, 2001), inhibited partially this proteolytic activity of MMP-9 (Fig. 2B, Lane 6).…”
Section: Mmp-9 Proteolyzes the Igfbp2-igfii Complexmentioning
confidence: 88%
“…TIMP-4, widely present in the normal central nervous system (CNS) (Crocker et al, 2004), has been reported to be overexpressed in indolent noninvasive pilocytic astrocytomas (WHO grade I) as compared with diffuse astrocytomas (WHO grade II-IV) (Rorive et al, 2006). TIMP-4 is also known to reduce the invasive ability of astrocytoma cells in vitro (Groft et al, 2001). In contrast, TIMP-1 is not observed in normal CNS, but its expression increases dramatically with astrocytoma malignancy (Groft et al, 2001;Lampert et al, 1998;Nakano et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIMP-1 is also involved in the development of neuroepithelial tumors (Gardner & Ghorpade, 2003;Lampert et al 1998;Kakagawa et al 1994;Pagentecher et al 1999). Groft et al (2001) showed that overexpression of TIMP-1 is associated with malignancy in gliomas and that TIMP-1 is detected mainly near the sites of blood vessel formation. These observations could be a result of interactions with pro-MMP-9 and the angiogenesispromoting ability of this MMP.…”
Section: The Role Of Timps In the Progression Of Astrocytic Tumorsmentioning
confidence: 99%